A study of common health problems and utilization of healthcare facilities among self-employed street vendors of Chandrapur district of Maharashtra - Meher, Sonu R.; Ghatole, Pushkar S. (International Journal Of Community Medicine And Public Health, 2020)
Background: In India, more than 90% of the workforce is engaged in the informal sector for their livelihoods. About 2-2.5% of the total urban population is involved in street vending, and out of the total urban population in the informal sector 14% is constituted of street vending. Unlike legalization, economic and working conditions of street vendors, there are little studies conducted to understand the health problems faced by them. Authors sought to study the common health problems and utilization of health care services among street vendors of Chandrapur district. Methods: It was a cross-sectional quantitative study. A total of 200 street vendors were purposively selected from four tehsils of the Chandrapur district and face to face interviews were conducted. Results: The common health problems among street vendors observed under this study were respiratory tract infections (32%), musculoskeletal problems (54.4%), gastrointestinal problems (18%), generalized weakness (12.7%), non-communicable diseases including hypertension, diabetes (26.6%). Among those who had suffered from these health problems, the majority (68%) utilized private healthcare facilities and 21% utilized public healthcare facilities. Conclusions: Though street vendors earn on daily basis, they seek healthcare services mostly from the private providers. This results in out-of-pocket expenditure for them. Therefore, it is essential to improve the overall quality of public healthcare facilities for curtailing the out of pocket expenditure. The study findings can be utilized to draw the attention of policymakers, in strategic planning the health care services for such low-income group.